2015 7th International Conference of Soft Computing and Pattern Recognition (SoCPaR) 2015
DOI: 10.1109/socpar.2015.7492818
|View full text |Cite
|
Sign up to set email alerts
|

Stream-based Particle Swarm Optimization for data migration decision

Abstract: As the load in the cloud environment is always changing, data migration become a key technology to realize the load balance of clusters. A good migration decision can make data migration more efficiency. To realize the migration decision rapidly, parallel Particle Swarm Optimization (PSO) based on stream computing technology is presented in this paper. We use PSO to get a migration plan with minimum overhead. Since the implementation of traditional PSO in serial is a huge waste of time in our scene, we design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…For example, MapReduce framework will restart the computing job when it the new data is coming. In our previous work,() we have explored some preliminary research on the improvement of PSO and have found the deficiency of batch processing in real‐time processing. For example, batch processing system has higher turnaround time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MapReduce framework will restart the computing job when it the new data is coming. In our previous work,() we have explored some preliminary research on the improvement of PSO and have found the deficiency of batch processing in real‐time processing. For example, batch processing system has higher turnaround time.…”
Section: Introductionmentioning
confidence: 99%